A new approach to simultaneously reducing, nitrogen doping and noble metal coating of graphene oxide via active-screen plasma. (29th January 2023) - Jing, Zhiyuan; Guo, Weiling; Yu, Helong; Qi, Shaojun; Tao, Xiao; Qiao, Yulin; Zhang, Wei; Li, Xiaoying; Dong, Hanshan
Abstract: Graphene is widely used for various applications, especially after nitrogen doping and incorporation with metal nanoparticles. Herein, a simultaneous approach to reducing, nitrogen doping and noble metals coating of graphene oxide (GO) is reported using an advanced active-screen plasma (ASP) technique. With a noble metal plate added as an extra lid of active screen cage, the corresponding noble metal, mainly or fully in pure metal state, depending on the noble metal type, as well as a minority of Fe and Cr, is deposited on GO with simultaneous reduction and nitrogen doping. The ASP treated GO exhibits varying levels of improvement in electrical property depending on the type of noble metal nanoparticles hybridized with. Specifically, ASP treated GO incorporated with Pt or Au revealed 2–4 orders of magnitude of improvement in electrical property.